2011
DOI: 10.1136/ip.2010.029124
|View full text |Cite
|
Sign up to set email alerts
|

Violence and social capital among young men in Beirut

Abstract: This research supports the literature that indicates that physical fights are positively related to both individual and social capital variables. Social capital had a detrimental effect on physical fights. This may be related to bonding in a gang-like way. While high levels of social capital are good for other health outcomes and thus should not be reduced, interventions that channel youth energy in positive ways are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…We asked about the proportion of the subject’s friends that shared his or her own ethnic background ( all or a lot , about half , none or very few ). Social capital is known to be related to violence, [35], [36] suicide [37] and mental health. [38] Given the constraints in the length of the survey, we selected questions a number of questions from the Office for National Statistics Social Capital Question Bank [39] in order to tap the most important elements of social capital of relevance to radicalisation.…”
Section: Methodsmentioning
confidence: 99%
“…We asked about the proportion of the subject’s friends that shared his or her own ethnic background ( all or a lot , about half , none or very few ). Social capital is known to be related to violence, [35], [36] suicide [37] and mental health. [38] Given the constraints in the length of the survey, we selected questions a number of questions from the Office for National Statistics Social Capital Question Bank [39] in order to tap the most important elements of social capital of relevance to radicalisation.…”
Section: Methodsmentioning
confidence: 99%
“…Social capital can be measured in many ways and is known to be associated with violence [30], [31], suicide [38] and mental health [39]. To measure social capital, we asked about satisfaction with living in the area (very satisfied, fairly satisfied, neither satisfied or dissatisfied, fairly dissatisfied, very dissatisfied), number of years living in a particular area (<1 year, 1 to <2 years, 2 to <5 years, 5 to <10 years, > or  = 10 years), how many people in local area can be trusted (many, some, a few or none), and feelings of safety when alone in the area after dark (very safe, fairly safe, fairly unsafe, very unsafe).…”
Section: Methods Sectionmentioning
confidence: 99%
“…This concept captures the assets, resources or ‘capital’ available to individuals and groups; it has been defined as community cohesion and resilience resulting from a rich associational life based on a strong array of co-operative social networks [11], [28]–[31]. Poor health and depressive symptoms can be a consequence of low social capital, isolation and inequalities, as well as experience of hardship, such as discrimination [32]–[34].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a cross-sectional study on social capital and adolescent behaviour using US data from 1994 to 1995, found that higher levels of participation in sports and club organizations actually increased tendencies towards fighting and the use of weapons (Wright and Fitzpatrick 2006). Additionally, a study on social capital and violence amongst young men in Beirut found that different indicators of social capital have ambiguous relationships with violence (El Hajj et al 2011). How can we explain the divergent effects of social capital on individual violence?…”
Section: Introductionmentioning
confidence: 99%